PUBLIC POLICY OF PUBLIC HEALTH PROTECTION OF UKRAINE IN THE CONDITIONS OF EUROPEAN INTEGRATION CHALLENGES - MATSYK, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article substantiates the relevance of building a progressive model of public policy of public health protection in Ukraine based on the need to overcome, on the one hand, a large number of long-standing obstacles, and, on the other hand, the influence of the war, the consequences of which are unpredictable and have already led to a critical state industry. The analysis of the latest researches and publications confirmed that the issues of public policy of public health protection in our country are given high attention by the scientific community and various methods of their effective solution are proposed. Public health is a determining factor in building a stable and competitive economy that primarily focuses on the needs of the population. The public policy of public health protection should be considered in relation to the ability of the country’s institutions to form the appropriate legal, organizational, economic and social framework in which they function. A mechanism for implementing the public policy of public health protection of Ukraine in the conditions of European integration challenges has been developed, the elements of which include subjects, objects, principles, functions, tools, measures, European integration challenges and goals. The public policy of public health protection should be considered in relation to the ability of the country’s institutions to form the appropriate legal, organizational, economic and social framework in which they function. The presented mechanism makes it possible to establish the basic necessary elements according to which the implementation of the public policy of public health protection is able to solve a full set of tasks for the formation of a progressive health care system in Ukraine according to European models. The processes of meeting the needs of the population in the preservation, protection and strengthening of health and well-being are clearly a priority in such a mechanism.
Keywords: public health; public policy; health care; European integration; people; state